Bombyx mori transcription factor, E74A, beneficially affects BmNPV infection through direct interaction. Issue 12 (12th September 2022) - Wang, Xin; Lv, Jun‐li; Cheng, Shuang; Su, Zhi‐hao; Qin, Sheng; Sun, Xia; Tang, Xu‐dong; Liu, Qiu‐ning; Li, Mu‐wang; Wang, Xue‐yang
Abstract: BACKGROUND: Nucleopolyhedrovirus (NPV), one of the baculoviruses, is a promising biopesticide for pest control. Lepidopteran account for 70% of pests, therefore investigation on highly conserved genes associated with viral infections in the lepidopteran model, the silkworm, will serve as a valuable reference for improving the effectiveness of pest management. BmE74A is a member of the erythroblast transformation‐specific (ETS) family of transcription factors in Bombyx mori, which we previously found to be highly conserved and closely associated with BmNPV. This study aimed to elucidate the role of BmE74A in viral infection. RESULTS: A significantly high expression of BmE74A in eggs indicated its important role in embryonic development, as did relatively high expressions in the hemolymph and midgut. Significant differences in BmE74A expression in different resistant strains after BmNPV infection suggested its involvement as a response to viral infection. Moreover, RNA interference (RNAi) and overexpression experiments confirmed the important role of BmE74A in promoting viral infection. BmNPV infection was significantly suppressed and enhanced by BmE74A knockdown and overexpression, respectively. Besides, BmE74A was found to regulate the expression of BmMdm2 and Bmp53 . Furthermore, the binding of ETS, the functional domain of BmE74A, to occlusion‐derived virus proteins was confirmed by far‐western blotting, and four viral proteins that may interact with ETS proteins were identified by mass spectrometry. Similarly, a homolog of BmE74A in Spodoptera litura was also found to be involved in larval susceptibility to BmNPV. CONCLUSION: BmE74A promotes BmNPV proliferation by directly interacting with the virus, which may be related to the suppression of the p53 pathway. © 2022 Society of Chemical Industry. Abstract : In this study, the important role of BmE74A in promoting BmNPV infection was confirmed by RNA interference and overexpression. Moreover, the interaction between ETS protein and ODV protein was confirmed by far‐western blot. Furthermore, the expression of BmMdm2 and Bmp53 was confirmed to be regulated by BmE74A . The results indicate that BmE74A benefits BmNPV proliferation by directly interacting with virus, and this might be related to the activation of the p53 pathway.